Mercury speciation in the Adriatic Sea. Issue 1 (15th July 2015) - Kotnik, Jože; Horvat, Milena; Ogrinc, Nives; Fajon, Vesna; Žagar, Dušan; Cossa, Daniel; Sprovieri, Francesca; Pirrone, Nicola
Highlights: Mercury and its speciation were studied in waters of the Adriatic Sea. Mercury concentrations were the highest in the northern part of the sea. Enrichment Hg in southward flowing and sinking surface water masses. A Hg mass balance was calculated based on these measurements and literature data. The Adriatic Sea is a net exporter of THg and MeHg to the Mediterranean. Abstract: Mercury and its speciation were studied in surface and deep waters of the Adriatic Sea. Several mercury species (i.e. DGM – dissolved gaseous Hg, RHg – reactive Hg, THg – total Hg, MeHg – monomethyl Hg and DMeHg – dimethylmercury) together with other water parameters were measured in coastal and open sea deep water profiles. THg concentrations in the water column, as well as in sediments and pore waters, were the highest in the northern, most polluted part of the Adriatic Sea as the consequence of Hg mining in Idrija and the heavy industry of northern Italy. Certain profiles in the South Adriatic Pit exhibit an increase of DGM just over the bottom due to its diffusion from sediment as a consequence of microbial and/or tectonic activity. Furthermore, a Hg mass balance for the Adriatic Sea was calculated based on measurements and literature data.